Spatiotemporal analysis framework for identifying emerging hot spots and energy potential from livestock manure in Turkey - (:unkn) unknown (My University, 2022)
Biogas technology offers both an environmentally sustainable solution for livestock manure and generates renewable energy. Renewable energy production from livestock manure highly depends on feedstock availability; therefore, the spatial and temporal variability of livestock manure is critical for its sustainable management via biogas plants. In this regard, this study aims to develop a replicable geographic information system based spatiotemporal method to determine emerging hot spots and power capacities for new biogas plants and capacity expansion for the existing plants. The method was conducted to analyze energy production from livestock manure at district level in Turkey between 2013 and 2019. Spatial dimension consists of 970 districts, which makes this study as the spatially most detailed investigation of energy potential from livestock manure in Turkey, while the temporal dimension consists of 13 time steps. 66 districts were determined as emerging hot spots in which 43 have no biogas plants. These hot spots were specified as districts with high priority for the installation of new biogas plants with power capacities ranging between 6.30 MWe and 22.54 MWe. The total theoretical power capacity was calculated as 640 MWe. Capacity expansions were calculated between 0.52 and 13.87 MWe for the existing 63 biogas plants. The unit cost of electricity generation from livestock manure via biogas plants was calculated greater than the feed-in tariff paid by the government. The method aids in decision-making process of environmentally and economically sustainable livestock manure management planning and biogas investors to direct their investments into profitable locations.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Engineering and Technology; ENERJİ VE YAKITLAR; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ENERGY & FUELS; ENGINEERING; Engineering, Computing & Technology (ENG); Enerji Mühendisliği ve Güç Teknolojisi; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Genel Mühendislik; Genel Enerji; Mühendislik (çeşitli); Yakıt Teknolojisi; Enerji (çeşitli); Fizik Bilimleri; Energy Engineering and Power Technology; Renewable Energy, Sustainability and the Environment; General Engineering; General Energy; Engineering (miscellaneous); Fuel Technology; Energy (miscellaneous); Physical Sciences; Biogas; Anaerobic digestion; Manure; GIS; Renewable energy; Spatial analysis; BIOGAS PRODUCTION; SPATIAL-ANALYSIS; ANIMAL MANURE; GENERATION; WASTES